Effects of an invasive crayfish on the littoral macroinvertebrates of large boreal lakes are habitat specific. (13th September 2013) - Ruokonen, Timo J.; Karjalainen, Juha; Hämäläinen, Heikki
Summary Invasive crayfish are widely acknowledged to have negative effects on benthic food webs in lakes, but few studies have investigated such effects at wider spatial scales and in varying habitats under natural conditions. We examined the effects of introduced signal crayfish (Pacifastacus leniusculus) on the macroinvertebrate assemblages of different habitats in two large boreal lakes. We evaluated whether the density, taxon richness and species composition are altered by the non‐native crayfish and whether the responses are similar for stony and vegetated habitats and across a depth gradient. We also studied the influence of crayfish on periphyton biomass at stony sites, as a potential link to changes in macroinvertebrate communities. In both lakes, macroinvertebrate density was similar between crayfish and non‐crayfish sites across the habitats and depths studied. However, macroinvertebrate taxon richness was significantly lower, and community composition was altered in the presence of crayfish at stony sites. No similar pattern was detected at vegetated sites or in deeper sublittoral areas. The amount of periphyton was similar regardless of the presence of crayfish, and no clear direct or indirect crayfish–periphyton interaction was detected. Our results suggest that introduced signal crayfish can have negative effects on the littoral macroinvertebrates of large boreal lakes, but that these effects are habitat specific. Our findings highlight how the evaluation of possible effects of invasive species needs to be carried out comprehensively across different habitats and spatial scales if conclusions are to be robust.